PENGEMBANGAN PERAN PEMBERDAYAAN MASYARAKAT BERBABIS KOMUNITAS - Hasad, Andi; Yulius, Elma (DEVOSI, 2020)
Economic improvement and development, of course, require the role of humans who drive the economy. Superior resources will improve the regional economy. In increasing the quality of superior human resources, it is necessary to develop through training in the form of development. The development program is expected to improve people's lives. Therefore, at a more operational level, development through the community empowerment process generally uses a community-based development approach. The results of the research that has been carried out by the PPM FT UNISMA Bekasi Team Activities for the 2018 period are expected to be a pioneer in the implementation of PPM activities as a form of partnership between FT UNISMA Bekasi and the Village / Kelurahan Government of Harapan Jaya and Mustika Jaya, Bekasi City. Therefore, it is hoped that it can become the basis for subsequent programs, especially for improving the quality of development in these two locations